Akomodasi Komunikasi pada Mahasiswa Sumatera dengan Mahasiswa Suku Jawa di Surakarta: (Studi pada Mahasiswa Sumatera di Universitas Slamet Riyadi) - Amelia, Kurnia; Riyanto, Buddy; Widiyowati, Estu (Solidaritas, 2024)
Slamet Riyadi University is a university that is the choice of overseas students from Sumatra to pursue education, even though it is far from their home area. As immigrants with different cultural backgrounds, they need to be able to adjust to the surrounding environment. Therefore, Sumatra students need communication accommodations to build good relationships with Javanese students. This research aims to describe the communication accommodations of Sumatra students with Javanese students in Surakarta city. This research uses Howard Giles' Theory of Communication Accommodation by examining convergence, divergence, and over-accommodation. This type of research is descriptive-qualitative, which describes the facts in the field with interview and observation techniques. The object of this research is Sumatra students at Slamet Riyadi University. The results showed that most of the Sumatran students made adjustments by convergence by adopting some Javanese language and adjusting to Javanese cultural norms, but a small number of Sumatra students made adjustments by divergence by emphasizing cultural identity such as speaking style and culture in Sumatra. Keywords: Communication accommodation, Sumatra students, Intercultural communication